2016
DOI: 10.1016/j.tet.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

An efficient method for the stereoselective synthesis of N-substituted trihydroxypiperidine derivatives promoted by p-TsOH

Abstract: a b s t r a c tAn effective and facile method for the synthesis of N-substituted trihydroxypiperidine derivatives is described. The Mannich-type reaction of protected 5-O-tosylate pentoses with amines and ketones in the presence of p-TsOH provides convenient access to the stereoselective synthesis of N-substituted iminosugar C-glycosides as potential glucosidase inhibitors in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…The synthesis of stereoselective bicyclic aza-sugar analogs was recently explored by Yuan et al 129 Subsequently, they 130 interestingly reported a stereoselective synthetic route for the preparation of hydroxy-piperidines and imino-sugar C -glycoside analogs. The products in this route are potent glycosidase inhibitors prepared in exceptional yields.…”
Section: Synthetic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of stereoselective bicyclic aza-sugar analogs was recently explored by Yuan et al 129 Subsequently, they 130 interestingly reported a stereoselective synthetic route for the preparation of hydroxy-piperidines and imino-sugar C -glycoside analogs. The products in this route are potent glycosidase inhibitors prepared in exceptional yields.…”
Section: Synthetic Approachesmentioning
confidence: 99%
“…Accordingly, the two possible products are known as Si -face and Re -face with the majority of Si -face products owing to the steric hindrance factor of the iso -propylidene group (Scheme 31). 130…”
Section: Synthetic Approachesmentioning
confidence: 99%
“…Interconversion between the piperidine derivatives and the tetrahydrofuran derivatives may also occur. In fact, previously reported reactions of iminium ions derived from sugar derivatives with ketones afforded tetrahydrofuran derivatives …”
mentioning
confidence: 99%
“…The use of less benzylamine also afforded 3a ; for example, in the reaction with 1.2 equiv of benzylamine to 1a , product 3a was obtained in 65% after 14 h (Scheme a). Reactions at 60 °C led the formation of tetrahydrofuran derivative 3aA as well as piperidine derivative 3a (Scheme b,c).…”
mentioning
confidence: 99%